`Thrombocytopenic serum': an artificial factor VIII-deficient reagent. Issue 2 (March 1964) - Davidson, E.; Tomlin, S.
Abstract : Thrombocytopenic serum is a simple reagent derived from platelet-poor plasma. The high levels of factor V and `zero' levels of factor VIII in this reagent make it a reliable alternative to haemophilia A plasma in the qualitative and quantitative assessment of factor VIII in the thromboplastin generation test.